Jogos eletrônicos, cultura juvenil e socialidade : a aprendizagem social virtual mediada e suas influências para a educação - Santos, Vinicius Silva (2011)
This research aims to study social learning mediated virtual as element conceptual relevance to education. The construction heuristic around social learning mediated virtual is as the theoretical framework of Sociology of Everyday Life developed by Michel Maffesoli. It is the study of the meanings attributed to video games by young people and their relationships with the concept of sociality, in order to understand the nature, characteristics and structure of contemporary learning as field of analysis taking the use and ownership of electronic games under the youth culture. The authors main were Maffesoli (1996, 2001, 2003, 2004, 2006, 2009), Assisi (2007), Gularte (2010), Mendes (2006), Santaella (2003, 2009), Buckingham (2007), Dubet (2004 ), Eagleton (2005), Levy (1996, 1999), Geertz (1989), Morin (1990, 1997), Assmann (1998), Baudrillard (1991), Maturana (1997), Hushkoff (1999), Deleuze and Guattari ( 1980) and Scheibe (2009), Vygotsky (1978), Stern and Willis (2010), Stephens (1993), Moraes (1997), Tapscott (2010), Gardner (1994). The research was conducted in the metropolitan area of Aracaju, in the period March 2009 to November 2010 through the participation of ten young people, aged 18-26 years, users of electronic games. The research methodology used is qualitative, interpretive paradigm, inspired by the research-based phenomenological hermeneutics. The research approach is ethnographic. The instruments of data collection used were: newspaper book, diary, participant observation and semistructured interview active. The results give prominence to social virtual mediated learning as a concept relevant, meaningful and relevant to the analysis of practices relating to school culture, crossed, especially by young people and their sense of expressive styles in the daily organization of pedagogical knowledge, largely influenced by elements of the culture outside the school environment, namely, electronic games, digital culture, the presence of virtual relationships in individual and collective elements of sociality and its influence in the organization of educational work through social learning mediated virtual.